The Effect of Mental Health and Psychosocial Support (MHPS)Training on The Public Awareness of New Habitual Adaptations (NHA): A Pilot Research - Susanti Niman; Habsyah Saparidah Agustina; Sri Wahyuni; Niken Yuniar Sari; Retty Octi Syafrini; Basmanelly Basmanelly; Ira Erwina; Komarudin Komarudin; Sukma Ayu Candra Kirana; Mad Zaini; Budi Anna Keliat; Rita Rahayu; Lahargo Kembaren (Jurusan Keperawatan FIKES UNSOED, 2021)
Background: The COVID-19 pandemic has a physical impact and on the mental health condition of the community. The existence of psychological distress due to the Covid 19 pandemic will affect the body's physiological conditions, such as reduced immune system responses and increased risk of infection, and the impact on mental health. The COVID-19 pandemic demands a change in people's behavior. Mental health and psychosocial support training is very important for the community so that the community can actively maintain mental and physical health. The research objective is to identify the effect of DKJPS training on awareness of new adaptation readiness. Method: The research was conducted through a quasi-experimental pre-post-test without control on 44 participants in the DKJPS training. Result: there is a significant difference between awareness of adaptation new habits before and after training (p-value 0.001). Conclusion: Mental health and psychosocial support training conducted in the community can increase public awareness of new adaptation habits independently.